Pengaruh Terapi Bermain terhadap Kemampuan Sosialisasi Anak Retardasi Mental - Indah Christiana; Aprilinda Safitri (Akademi Kesehatan Rustida, 2021)
Mentally retarded children tend to have problems in social adaptation. The effects of social limitations that are not immediately addressed in mentally retarded children can affect their psyche, such as; social disorders, easily frustrated, anxious, and easily afraid. Socialization skills that are less adaptive in mentally retarded children can be overcome by non-pharmacological therapy, namely play therapy. The purpose of this literature review is to determine the effect of play therapy on the socialization ability of mentally retarded children. The method used is meta-analysis by searching for articles using PICOT questions on the Google Scholar database and Garuda Portal. The search was limited to full-text articles, in Indonesian and English, published in 2010-2020 and further identification and screening were carried out. Based on the results of the literature review article search, 8 articles were found that matched the inclusion and exclusion criteria. All of these journal articles prove that play therapy can affect the socialization ability of mentally retarded children. Play therapy can be used as an alternative therapy for mentally retarded children to improve socialization skills.